A succession of dialogues: François-Marie Luzel and his contribution to the Breton folk tale. Issue 1 (1st August 2019) - Wilson, Michael
François-Marie Luzel (1821–95) was one of the most significant French folklorists of his day and champion of Breton culture. He mainly collected folk tales in his native Lower Brittany and published prolifically, including three volumes in the monumental Contes populaires series, published by Maisonneuve and Charles Leclerc in 1887. On the one hand, Luzel was a man of his time, adopting the philosophies and approaches of his fellow folklorists and antiquarians. However, many of his methods, in particular his insistence on authenticity and fidelity to the spoken word, and his realization that traditional cultures are enriched and preserved not through cultural isolation, but by interaction with other cultures, seem out of step with the attitudes of many of his contemporaries and rather seem to anticipate twentieth-century developments in folk tale collecting practice. Furthermore, Luzel often courted controversy and regularly came into conflict with many of his colleagues in the Breton cultural and political establishment around his insistence on publishing in French and his attitude towards the literary 'Unified Breton' and the associated debates around what constituted an authentic Breton culture. This article will place Luzel in his historical context and explore his approach to collecting and publishing his folk tales and the controversies that he courted. It is followed by a companion piece – a new translation of one of Luzel's tales – 'Jannic aux deux sous' ('Tuppenny Jack') – a Breton variant of 'The Frog Prince'.